Mesial temporal sclerosis presented with refractory seizure - Malav Patel; Rishika Reddy; Sangram Biradar; V H Kumarswamy (Wolters Kluwer Medknow Publications, 2019)
Background: Refractory complex partial seizures are common in temporal lobe epilepsy, which is often associated with sclerosis of the structures of the medial temporal lobes, particularly the hippocampus. This abnormality is one of the most prevalent epileptogenic foci in localization-related epilepsy. Here we report a case of mesial temporal sclerosis with refractory seizures. Case presentation: A 69 year old diabetic male presented with history of 3 episodes of seizures, and was brought to hospital in a state of confusion. Patient was a known case of epilepsy on treatment. MRI brain revealed Left medial temporal sclerosis. Conclusion: Mesial temporal sclerosis is a pathologic entity associated with refractory temporal lobe epilepsy (TLE). Surgical resection is the treatment of choice in appropriate candidates